Engineers Employability Competency: Employer Perspective - Hasan, Hazmilah; Dunn, Ian; Jones, Ray (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2008)
The objectives of this study is to assess whether the suggested lack of interpersonal and enterprise skills competencies cause unemployment amongst engineering graduates in Malaysia. Critically appraise if engineering undergraduates have received a quality work placement (appropriate to their learning, knowledge and employability skills) and to enhance in interpersonal and enterprise skills competencies awareness amongst engineering undergraduates in Malaysia. This study will employ qualitative method. An interview questionnaire adapted from Course Experience Questionnaire (CEQ), Australia (Ramsden, 1991) and combination of L. Harvey (2001), generic skill criteria for workplace framework will be utilized to suit the research purpose. The result from the interview will be interpreted. The qualitative result revealed that the employers generally had delivered working exposure to the industrial training trainees.